Comparative identification and evolutionary relationship of fatty acid desaturase (FAD) genes in some oil crops: the sunflower model for evaluation of gene expression pattern under drought stress - Celik Altunoglu, Yasemin; Unel, Necdet Mehmet; Baloglu, Mehmet Cengiz; Ulu, Ferhat; Can, Tevfik Hasan; Cetinkaya, Rahmi (Informa UK Limited, 2018)
Sunflower (Helianthus annuus L.) and some oil crops have considerable economic value, making them important for commercial use. The fatty acid content of their seeds is crucial for proper nutrition. Additionally, the desaturation reaction via fatty acid desaturases (FADs) leads to formation of double bonds in fatty acids and is an essential step in fatty acid biosynthesis. This study aimed to identify and compare some fatty acid desaturase gene members in sunflower and other oil crops. Totally, 33 FAD genes from sunflower, 19 from sesame, 20 from canola, 25 from cacao and 46 from flax were analysed. The FAD members had roles in oxidation–reduction processes, fatty acid biosynthetic processes or lipid metabolic processes. Comparative phylogenetic and motif analysis revealed a conserved structure among FAD members belonging to various oil crops. The average Ka/Ks rates calculated on the basis of orthologous gene analysis were 0.04, 0.05 and 0.05 between sunflower and, respectively, canola, cacao and sesame. The most recent divergence time between sunflower and cacao was estimated at an average of 100 million years ago (MYA). This was followed by flax, sesame and canola with an average of 101 MYA, 114 MYA and 149 MYA, respectively. Alpha-helices were dominant in the predicted 3D structures of FAD proteins. The FAB2 expression levels from a drought tolerant sunflower variety were not affected by drought. The characterisation of desaturase family members in economically valuable oil crops could be useful for functional cloning studies to enhance the unsaturated fatty acid contents of the plants.
Keywords: Sunflower; oil crops; fatty acid desaturase enzyme (FAD); genome wide determination; TP248.13-248.65; Biotechnology; 2. Zero hunger; 15. Life on land; 6. Clean water